1999
DOI: 10.1037/1076-8998.4.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traumatic incidents and prevalence of posttraumatic stress symptomatology in urban firefighters in two countries.

Abstract: Urban firefighters are at risk for posttraumatic stress disorder (PTSD) due in part to their exposure to duty-related trauma. This study compared duty-related trauma exposures and the prevalences of posttraumatic stress in U.S. and Canadian firefighters. Both samples reported relatively numerous and frequent posttrauma symptoms, and the rates of self-reported PTSD prevalence did not differ significantly. However, analysis of departmental records for respondents' previous year on duty revealed significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
274
5
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(298 citation statements)
references
References 18 publications
11
274
5
8
Order By: Relevance
“…Our findings also agree with previous research which found that social support from both work and family sources ameliorated stress and was protective against distress for police officers and firefighters. [44][45][46] LIMITATIONS A number of limitations should be kept in mind when interpreting our results. Our study was conducted using a convenience sample, which may limit the ability to generalize our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also agree with previous research which found that social support from both work and family sources ameliorated stress and was protective against distress for police officers and firefighters. [44][45][46] LIMITATIONS A number of limitations should be kept in mind when interpreting our results. Our study was conducted using a convenience sample, which may limit the ability to generalize our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Operational experience, i.e. years of service, has not been associated with growth (Chopko, 2010) but has been either positively associated (Corneil et al, 1999) or not associated at all (Clohessy & Ehlers, 1999;Corneil et al, 1999) with post-event distress.…”
Section: Person Pre-event Characteristicsmentioning
confidence: 86%
“…However, previous research had suggested that an effect of gender on post-event distress would be less detectable in samples of emergency and also military personnel than in the general population (Brewin et al, 2000;Corneil et al, 1999). Indeed, a recent study with DISTRESS AND GROWTH AMONG FIREFIGHTERS 16 civilian fire survivors revealed that females reported experiencing higher distress levels during the event than their male counterparts (Knuth, Kehl, Hulse, & Schmidt, 2013).…”
Section: Person Pre-event Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…The requirements inherent to the profession often put the firefighter in borderline situations in terms of exposure to potentially traumatic stress events (Corneil, Beaton, Murphy, Johnson & Pike, 1999). Therefore, it is not surprising that a significant percentage of firefighters develop mental disorders subsequent to traumatic experiences (Bennett et al, 2005; Centers for Disease Control and Prevention, 2006).…”
Section: Firefighters and Mental Health/illnessmentioning
confidence: 99%